Landscapes with different logics: A physicalistic approach to semantic conflicts in spatial planning - Krzysztofik, Robert; Dymitrow, Mirek; Biegańska, Jadwiga; Senetra, Adam; Gavriilidou, Eleftheria; Nadolu, Bogdan; Kantor-Pietraga, Iwona; Grzelak-Kostulska, Elżbieta; Oureilidou, Eleni; Luches, Daniel; Spórna, Tomasz; Teodorescu, Dominic; et al. (Quaestiones Geographicae, 2017)
This paper deals with the ways of categorising landscapes as ‘urban’ and ‘rural’ using a physicalist approach, where these terms have special meaning. The aim of this paper is to elaborate on the question whether such a division is still meaningful with regard to anthropogenic landscapes, not least in spatial planning. The concerns raised in this paper depart from the increasingly complicated structure of geographical space, including that of anthropogenic landscapes. Our standpoint is illustrated using cases of landscape ambiguities from Poland, Germany, Romania and Greece. Leaning on frameworks of physicalist (mechanicistic) theory, this paper suggests an explanation to the outlined semantic conflicts. This is done by pointing to the relationality between the impact of centripetal and centrifugal forces, the specifics of socio-economic development, as well as the varying landscape forms that emerge from the differences within that development.